1986
DOI: 10.1111/j.1745-4557.1986.tb00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adjuncts on Restructured Pork

Abstract: Boneless pork shoulders were excised 24h postmortem, frozen, tempered, jlaked and blended with one of the four fomulations: (1) 1 % NaCl and .25 % sodium tripolyphosphate (STP); (2) .5% NaCl, .5% KCl and .25% STP; (3) 1% NaC1, ,25% STP and -125% lecithin; or (4) .5% NaCl, .5% KCl, .25% STP and .125 % lecithin. 7he blended samples were converted to restructured chops and stored at -18C until evaluated at 5, 14 and 56 days. Appearance and taste attributes were measured objectively and subjectively. Objective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They found as the chain length of the phosphate increased, the extent of the synergistic effect between the salt and the phosphates decreased linearly. Marriott, Korzon, Boling, and Graham (1986b) found that storage time affected the color and other visual traits more than the adjuncts in frozen storage tests. Miller, Davis, Seideman, Ramsey, and Rolan (1986a) studied seven blends of restructured beef steaks, with different level of phosphate salts.…”
Section: Phosphatesmentioning
confidence: 99%
“…They found as the chain length of the phosphate increased, the extent of the synergistic effect between the salt and the phosphates decreased linearly. Marriott, Korzon, Boling, and Graham (1986b) found that storage time affected the color and other visual traits more than the adjuncts in frozen storage tests. Miller, Davis, Seideman, Ramsey, and Rolan (1986a) studied seven blends of restructured beef steaks, with different level of phosphate salts.…”
Section: Phosphatesmentioning
confidence: 99%